2020
DOI: 10.1101/2020.05.03.20081380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Influencing Mental Health During Covid-19 Outbreak: An Exploratory Survey Among Indian Population

Abstract: Purpose: Research on the impact of social distancing on mental health during epidemics is limited, especially in India. The purpose of this study is to scale the association between anxiety and socio-demographic factors during Covid19 lockdown among the general Indian population.Design/methodology/approach: A descriptive cross-sectional nationwide study was designed to enrol the general population. The inclusion criteria for this study were Indian citizens aged 18 years and above. The study was conducted from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…In times of COVID-19, a survey from India showed that married participants had 40% lower odds of developing anxiety during COVID-19 lockdown than unmarried participants [6]. Yet, the following examples show that the relationship between marriage / relationship and mental health seems to be moderated by marriage / relationship quality [7].…”
Section: Introductionmentioning
confidence: 94%
“…In times of COVID-19, a survey from India showed that married participants had 40% lower odds of developing anxiety during COVID-19 lockdown than unmarried participants [6]. Yet, the following examples show that the relationship between marriage / relationship and mental health seems to be moderated by marriage / relationship quality [7].…”
Section: Introductionmentioning
confidence: 94%
“…The question item 21, 17, 16, 13, 10, 5, and 3 were items of the depression subscale. The score of depression subscale was Normal (0-9), Mild depression (10)(11)(12), Moderate depression (13)(14)(15)(16)(17)(18)(19)(20), severe depression (21)(22)(23)(24)(25)(26)(27), and Extremely severe depression (28-42). Questions item 20, 19, 15, 9, 7, 4, and 2 were items of the anxiety subscale.…”
Section: Data Collection Procedures and Instrumentsmentioning
confidence: 99%
“…Questions item 20, 19, 15, 9, 7, 4, and 2 were items of the anxiety subscale. The score of anxiety subscale was Normal (0-6), Mild (7-9), Moderate (10)(11)(12)(13)(14), Severe (15)(16)(17)(18)(19), and extremely severe . Questions items 18,14,12,11,8,6, and 1 were items of the stress subscale.…”
Section: Data Collection Procedures and Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations